New Teachers for a New Century Recommendations from a National Invitational Conference (Racine, Wisconsin, November 17-19, 1999) - National Research Center on Education in the Inner Cities, Philadelphia, PA.; Lahr-Vivaz, Elena; National Research Center on Education in the Inner Cities, Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This collection of papers includes: "New Teachers for a New Century: Recommendations from a National Invitational Conference" (Margaret C. Wang and Herbert J. Walberg); "Teacher Quality, Teacher Effectiveness: Basing Education Policy on the Facts" (Arthur E. Wise); "Accreditation Reform and the Preparation of Teachers for a New Century" (Frank B. Murray); "The Union's Role in Ensuring Teacher Quality" (Sandra Feldman); "A Commitment to Quality: NEA's Efforts To Improve Teaching in America" (Bob Chase); "Teaching Perspectives of Exemplary Teachers" (Edna M.J. Littlewood); "The Teachers We Need and How To Get More of Them: A Manifesto" (Chester E. Finn, Jr. and Marci Kanstoroom); "Regulation Versus Markets: The Case for Greater Flexibility in the Market for Public School Teachers" (Michael Podgursky); "Ten Years of Teach For America: Our Record and Learning" (Wendy Kopp); "Generic Aspects of Effective Teaching" (Jere Brophy); "Promising New Instructional Practices" (Phyllis Blumenfeld, Joseph S. Krajcik, Ronald W. Mars, and Elliot Soloway); "Getting To Highest-Priority Outcomes: Designing Urban Preparation Programs for all Teacher Candidates" (Victoria Chou and Mary Bay); and "Quality Teachers Through Regional Collaboration" (Diana Wyllie Rigden). (SM)
Availability: CEIC, Temple University Center for Research in Human Development and Education, 1301 Cecil B. Moore Avenue, Philadelphia, PA 19122-6091. Tel: 215-204-3000. For full text: http://www.temple.edu/LSS/pubsz/htm.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
ERIC Note: Theme issue. Conference cosponsored by the Johnson Foundation and the Laboratory for Student Success, Temple University Center for Research in Human Development and Education.
CEIC Review, v9 n1 Feb 2000.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Teacher Induction; Diversity (Student); Educational Policy; Educational Quality; Educational Research; Elementary Secondary Education; Higher Education; Inservice Teacher Education; Minority Groups; Poverty; Preservice Teacher Education; Teacher Certification; Teacher Effectiveness; Teacher Recruitment; Teachers; Teaching Methods; Unions; Urban Education; Teach for America; Collected Works, Proceedings; Collected Works, Serials